UK AMD EMR USERS GROUP REPORT V: benefits of initiating ranibizumab therapy for neovascular AMD in eyes with vision better than 6/12. Issue 8 (13th February 2015) - Lee, Aaron Y; Lee, Cecilia S; Butt, Thomas; Xing, Wen; Johnston, Robert L; Chakravarthy, Usha; Egan, Catherine; Akerele, Toks; McKibbin, Martin; Downey, Louise; Natha, Salim; Bailey, Clare; et al.
Abstract : Background/aims: To study the effectiveness and clinical relevance of eyes treated with good (better than 6/12 or >70 Early Treatment Diabetic Retinopathy Study letters) visual acuity (VA) when initiating treatment with ranibizumab for neovascular age-related macular degeneration (nAMD) in the UK National Health Service. Currently eyes with VA better than (>) 6/12 are not routinely funded for therapy. Methods: Multicentre national nAMD database study on patients treated 3–5 years prior to the analysis. Anonymised structured data were collected from 14 centres. The primary outcome was the mean VA at year 1, 2 and 3. Secondary measures included the number of clinic visits and injections. Results: The study included 12 951 treatment-naive eyes of 11 135 patients receiving 92 976 ranibizumab treatment episodes. A total of 754 patients had baseline VA better than 6/12 and at least 1-year of follow up. Mean VA of first treated eyes with baseline VA>6/12 at year 1, 2, 3 were 6/10, 6/12, 6/15, respectively and those with baseline VA 6/12 to >6/24 were 6/15, 6/17, 6/20, respectively (p values <0.001 for comparing differences between 6/12 and 6/12–6/24 groups). For the second eyes with baseline VA>6/12, mean VA at year 1, 2, 3 were 6/9, 6/9, 6/10 and those with baseline VA 6/12 to >6/24 were 6/15, 6/15, 6/27, respectively (p values <0.001–0.005). There was no significant difference in the average number of clinic visits or injections between those with VA better and worse than 6/12. Conclusions: All eyes with baseline VA>6/12 maintained better mean VA than the eyes with baseline VA 6/12 to >6/24 at all time points for at least 2 years. The significantly better visual outcome in patients who were treated with good baseline VA has implications on future policy regarding the treatment criteria for nAMD patients' funding.